Kontribusi Pemikiran Nahwu Imam Sibawaih dan Ibrahim Mushtafa dalam Linguistik Arab - Andi Holilulloh (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2020)
This paper analyses the development of Arabic Syntax, starting from classical period up to modern one which is intuitively synthesis-pragmatic. The epistemology of classical and modern Arabic syntax is focused on the thoughts of Imam Sībawaih and Ibrāhīm Muṣṭafā to represent each A’jam and ‘Arab. This research uses the method of epistemology-comparative-history with procedure of intertext analysis. Method used by classical figures to compile Naḥwu are samāʻī, qiyāsī, ijmā’, taʻlīl, ta'wīl, istiḥsān and istiṣḥāb with both philosophical and theological approaches. Meanwhile, methods used by modern figures in compiling Naḥwu is tanẓīriyyah and taṭbīqiyyah. This research confirms what researchers explain that the contribution of Sībawaih to the development of Naḥwu lays on the classification of i’rab for noun (ism) into raf ‘, naṣb and khafd. This so-established theory is simplified by Ibrāhīm Muṣṭafā who says that iʻrāb consists of dammah and kasrah. He does not take fathah into account of i'rab.